Discourse Study and Analysis on Koran and Bible - Azam Parcham (Comparative Theology, 2010)
Nowadays, all Cultivated thinkers and believers in divine religions see the dialogue among religious as necessary task in order to attain the religious and human co-existence and mutual understanding. They believe that such dialogues will bring about a sense of sympathy and a true knowledge of religion. It is clear that core of such dialogues are the revealed Scriptures. Among these Scriptures, the Holy Koran and the Bible, Possessing the greatest number of believers in the world, are the main focus of the inter- religious dialogues.